Lunch with a bigot : the writer in the world - Kumar, Amitava, 1963- (Duke University Press, 2015)
The twenty-six essays in Lunch With a Bigot are examples of how Amitava Kumar turns his observations of the world into words. A mix of memoir, reportage, thoughts on the craft of writing, and criticism, these essays tell broad stories of immigration, change, and a shift to a more globalized existence.